Initial in vivo experience with a novel type of MR-Safe Pushable Coils for MR-Guided Embolizations - Homagk, Ann-Kathrin Verena; Umathum, Reiner; Bock, Michael; Hallscheidt, Peter (Investigative radiology, 2013)
Objective - Conventional detachable embolization coils are made from platinum or stainless steel and may thus be a magnetic resonance (MR) safety hazard because of resonant device heating. The objective of this experimental study was to assess the feasibility of MR-guided embolization procedures with a novel type of nonmetallic and, therefore, intrinsically MR-safe pushable coil. - Materials and Methods - The embolization coils are made from a polymer and coated with a hydrogel, which expands during contact with liquids. Magnetic resonance-guided embolizations were performed in 6 healthy domestic pigs by deploying up to 3 polymer pushable coils via an active tracking catheter under real-time magnetic resonance imaging monitoring. To assess the renal perfusion deficit induced by the coil embolization, intra-arterial 3-dimensional contrast-enhanced magnetic resonance angiography (3D ce-MRA) data sets were acquired before and every 5 minutes after coil placement until complete vessel occlusion. - Results - The MR-guided embolizations were successful in 5 of the 6 animals. The 3D ce-MRA data sets indicated first perfusion deficits within 2 to 40 minutes after coil deployment. Complete vessel occlusion was achieved after 6 to 53 minutes. In 1 animal, no perfusion defect could be detected. Because our experiments were designed as a preliminary proof-of-concept study, different sizes and numbers of all-polymer hydrocoils were deployed at different anatomical positions, making the drawing of correlation between the size/number of deployed coils and the occlusion efficiency difficult. The all-polymer hydrocoils did not induce any artifacts on the MR images, either in the real-time MR images, which were recorded during the embolization, or in the subsequently acquired 3D ce-MRA images. - Conclusions - Our results demonstrated that the novel all-polymer and intrinsically MR-safe pushable hydrocoils may become a promising tool for MR-guided embolization procedures.
Gesehen am 21.09.2021